Pengaruh Ukuran Perusahaan, Kualitas Audit, Dan Kepemilikan Asing Terhadap Keterjadian Restatement Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2015-2019 - Rizki Dwi Anggara; Emilia Gustini; R.M. Rum Hendarmin (Journal of Accounting and Taxation, 2023)
This study aims to determine the effect of company size, audit quality, and foreign ownership on the occurrence of restatements in food and beverage companies listed on the Indonesia Stock Exchange (BEI) 2015-2019. The data used in this study were obtained from the results of literature studies and documentation studies. The sample was selected using a purposive sampling technique. The data for 65 samples were analyzed using multiple linear regression. The results of this research support the idea that company size, audit quality, and foreign ownership had a significant effect on the restatement. Simultaneously the variables of company size, audit quality, and foreign ownership have a significant effect on restatement in food and beverage companies listed on the Indonesia Stock Exchange (BEI) 2015-2019.